Determinants of Poverty in the Special Region of Yogyakarta: A Panel Data Analysis Approach - Bakhri Muh Syaiful; Nasrulloh Amin; Pratista Dian (SHS Web of Conferences, 2025)
The objective of this research is to examine the factors influencing poverty in the Special Region of Yogyakarta Province between 2015 and 2023. The investigation utilises panel data from six administrative areas, comprising Kulon Progo Regency, Bantul Regency, Gunung Kidul Regency, Sleman Regency, and Yogyakarta City. The study considers three primary variables affecting poverty rates: Education Level, Unemployment, and Human Development Index. Employing panel data regression through the Eviews 9 software, the research adopts a Fixed Effect Model (FEM) approach. The findings reveal that Education Level and Human Development Index demonstrate a significant negative correlation with poverty, whilst Unemployment exhibits a significant positive relationship with poverty levels in the Special Region of Yogyakarta.